THE INFLUENCES OF JAVANESE CULTURE IN POWER OF MAKING DECISIONS IN INDONESIAN UNIVERSITIES: CASE STUDIES IN MM PROGRAMMES - Santoso, Budi (Journal of Indonesian Economy and Business, 2012)
This study aims to explore the influence of Javanese cultural values in power of the processes of making decisions in the Indonesian university settings. The case-study methodis used in this study. The choice of particular universities in Yogyakarta and Surakarta to be studied is based on a number of criteria, namely, location in central Java, accredited and non-accredited institutions, similarity of programmes and the year of foundation, and ease of access by this study, to obtain one-to-one interviews. The findings show that Javanese cultural values, including loyalty to the top level of the hierarchy, obedience to superiors and the desire for conflict avoidance are power to control the decision-making processes in the universities. Furthermore, the practice of using that power is maintained because of social acceptance. However, the findings do not represent a model of the healthy institution in which autonomy and empowerment are emphasized on.Keywords: Javanese culture, founding fathers, loyalty, obedience, seniority, and case study